PERAMALAN VOLUME IMPOR MIGAS DI INDONESIA MENGGUNAKAN METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE - Latupeirissa, Indri Kezia; Laamena, Novita Serly; Bustan, Ariestha W; Talib, Taufan (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2024)
Indonesia is one of the countries with abundant natural resources. Mining is one of the most important factors that need to be maintained to improve the welfare of its people and also contributes to the majority of state revenues in the non-tax sector, such as oil and gas. The development of Indonesia's oil and gas sector is very dynamic. Indonesia and countries in the world must adjust production, consumption, domestic and foreign policies from time to time due to changes in world oil prices in order to achieve people's welfare. In addition, our oil and gas production and reserves will continue to decline over time, so we have to import oil and gas. The increase in oil and gas imports also has an impact on the strengthening of the Rupiah exchange rate, so that demand for domestic currency also increases. Therefore, it is necessary to have a forecast to determine the volume of oil and gas imports in Indonesia for the next year. This study aims to predict the volume of oil and gas imports in Indonesia using one of the time series forecasting methods, namely the ARIMA method. The data used is oil and gas import data from January 2019 to December 2023 sourced from the Central Statistics Agency. The results of the study show that the right method for oil and gas import data is the ARIMA Model (0,1,1). The forecast results from January to June 2024 are 4557.45 tons, 4582.71 tons, 4608.04 tons, 4633.44 tons, 4658.91 tons and 4684.45 tons. The MAPE value of 9.31% indicates that the forecast results are very accurate